O pensamento computacional e as contribuições para o estudo da álgebra no ensino fundamental - Schneider, Camila (2020)
The present work is a research about algebra and computational thinking in elementary school. The central research question is How can the teaching of algebra contribute to the development of computational thinking in 8th grade students. Thus, 64 students from the 8th grade of elementary school of a private school in Rio Grande do Sul participated in this study. The research had a qualitative approach and the type of research was the case study, where data collection was performed by through activities produced by the students. A questionnaire with open questions was also applied, which was analyzed through Discursive Textual Analysis (ATD). From ATD, three categories of analysis emerged. The results show that students understand the relationship between algebra and computational thinking through algebraic expressions and algorithms, and that computational thinking contributes to a better understanding of algebra. Research has also shown that some students perceive the four pillars of computational thinking as a way of relating algebra to computational thinking. Thus, computational thinking in math classes opened the possibility of different algebra classes. It also contributed to the learning of students in the subject and computational thinking proved to be efficient for developing computer science in elementary school.